T-Cell Receptor Rearrangement by Whole-Genome Sequencing and Copy Number Variation Analysis - A Novel Marker of T cell Clonality - Oon, Ming Liang (NATURE PUBLISHING GROUP, 2022)
109th Annual Meeting of the United-States-and-Canadian-Academy-of-Pathology (USCAP)